161k views
2 votes
Find the product.

(a^2-b)(5a^2+6b)

2 Answers

1 vote
You can find the product of this by performing FOIL.

F (first) = a^2 * 5a^2 = 5a^4
I (inner) = -b * 5a^2 = -5a^2b
O (outer) = a^2 * 6b = 6a^2b
L (last) = 6b * -b = -6b^2

All that is left is to combine and simplify (is possible):

5a^4 -5a^2b + 6a^2b -6b^2
5a^4 + a^2b -6b^2

The final answer for this problem is:

5a^4 + a^2b -6b^2

Hope this helps!
User Tony Cesaro
by
5.9k points
2 votes

Answer:


( {a}^(2) - b)(5 {a}^(2) + 6b) \\ 5 {a}^(4) + 6 {a}^(2) b - 5 {a}^(2) b - 6 {b}^(2) \\ = 5 {a}^(4) + {a}^(2) b - 6 {b}^(2)

User Infamoustrey
by
5.3k points